A Cadaveric Evaluation of Pin and Tension Band Configuration Strength for Tibial Tuberosity Osteotomy Fixation - Zide, Amy N.; Jones, Stephen C.; Litsky, Alan S.; Kieves, Nina R. (Veterinary and Comparative Orthopaedics and Traumatology, 2020)
Objective The purpose of this study was to compare the load at failure and mode of failure of four constructs used to stabilize a tibial tuberosity osteotomy, including two vertically aligned pins (V), two horizontally aligned pins (H), two vertically aligned pins with a tension band wire (V-TB) and two horizontally aligned pins with a tension band wire (H-TB).Study Design Eighteen pairs of cadaveric tibiae were randomized to receive a TB or no TB. One limb was randomized to be in the H or V group. The contralateral limb was then assigned to the opposite configuration. One pair of limbs was used as a control. A tensile force was applied to the patellar ligament until construct failure.Results There was no significant difference between the mean load at failure of the H (595 N) and V (556 N) groups or between H-TB (1032 N) and V-TB groups (1034 N) (p = 0.487 and p = 0.238, respectively). The TB constructs were significantly stronger than the pin only constructs (p < 0.001). The mode of failure was similar for the pin only constructs, regardless of pin orientation. The TB constructs and control tibias failed at similar loads, most commonly by patellar ligament rupture.Conclusion The use of vertically aligned pins versus horizontally aligned pins does not affect construct strength. These results support the placement of pins in a vertically or horizontally aligned fashion. When performing a tibial tuberosity osteotomy, the addition of a TB adds significant strength to the construct.
Keywords: tibial tuberosity transposition; patellar luxation; mechanical testing; tension band wire; dog